Siderophile element constraints on the thermal history of the H chondrite parent body. (15th January 2019) - Archer, Gregory J.; Walker, Richard J.; Tino, Jonathan; Blackburn, Terrence; Kruijer, Thomas S.; Hellmann, Jan L.
Abstract: The abundances of highly siderophile elements (HSE: Re, Os, Ir, Ru, Pt, Pd), as well as 187 Re- 187 Os and 182 Hf- 182 W isotopic systematics were determined for separated metal, slightly magnetic, and nonmagnetic fractions from seven H4 to H6 ordinary chondrites. The HSE are too abundant in nonmagnetic fractions to reflect metal-silicate equilibration. The disequilibrium was likely a primary feature, as 187 Re- 187 Os data indicate only minor open-system behavior of the HSE in the slightly and non-magnetic fractions. 182 Hf- 182 W data for slightly magnetic and nonmagnetic fractions define precise isochrons for most meteorites that range from 5.2 ± 1.6 Ma to 15.2 ± 1.0 Ma after calcium aluminum inclusion (CAI) formation. By contrast, 182 W model ages for the metal fractions are typically 2–5 Ma older than the slope-derived isochron ages for their respective, slightly magnetic and nonmagnetic fractions, with model ages ranging from 1.4 ± 0.8 Ma to 12.6 ± 0.9 Ma after CAI formation. This indicates that the W present in the silicates and oxides was not fully equilibrated with the metal when diffusive transport among components ceased, consistent with the HSE data. Further, the W isotopic compositions of size-sorted metal fractions from some of the H chondrites also differ, indicating disequilibrium among some metal grains. The chemical/isotopic disequilibrium of siderophile elements among H chondrite components is likely the result of inefficient diffusion of siderophile elements from silicates and oxides to some metal and/or localized equilibration as H chondrites cooled towards their respective Hf-W closure temperatures. The tendency of 182 Hf- 182 W isochron ages to young from H5 to H6 chondrites may indicate derivation of these meteorites from a slowly cooled, undisturbed, concentrically-zoned parent body, consistent with models that have been commonly invoked for H chondrites. Overlap of isochron ages for H4 and H5 chondrites, by contrast, appear to be more consistent with shallow impact disruption models. The W isotopic composition of metal from one CR chondrite was examined to compare with H chondrite metals. In contrast to the H chondrites, the CR chondrite metal is characterized by an enrichment in 183 W that is consistent with nucleosynthetic s -process depletion. Once corrected for the correlative nucleosynthetic effect on 182 W, the 182 W model age for this meteorite of 7.0 ± 3.6 Ma is within the range of model ages of most metal fractions from H chondrites. The metal is therefore too young to be a direct nebular condensate, as proposed by some prior studies.